Endocrine abnormalities in dilated cardiomyopathy - Ankit Jain; S Ramakrishanan; Rajesh Khadgawat (Journal of the Practice of Cardiovascular Sciences, 2015)
Background: Progress has been made in the understanding of cellular and molecular mechanisms of hormone action and its effects on the cardiac tissue. There is evidence from observational studies that patients with postpartum cardiomyopathy improve after inhibition of release of prolactin from the pituitary by bromocriptine. This has renewed interest in the role of hormones in the pathogenesis of cardiomyopathy, especially in women. We intended to assess the hormonal changes in female patients with dilated cardiomyopathy (DCM). Methods: Twenty female patients aged 20-40 years old (mean age 29 ΁ 5.6 years) with a diagnosis of idiopathic DCMP with left ventricular ejection fraction [EF] <35% and a stable clinical course in the last 3 months were included in the study. All the patients were in New York Heart Association (NYHA) Class II or III. All the patients underwent clinical evaluation followed by blood sampling for hormonal analysis. Blood was taken after overnight fasting and analyzed for thyroid stimulating hormone (TSH), T3, T4, insulin-like growth factor I (IGF-I), prolactin, insulin, parathyroid hormone (PTH), and 25 (OH) Vitamin D. The results were compared with twenty age and sex matched controls. Results: The mean EF of the twenty patients was 24.4 ΁ 5.3% and duration of symptoms was 29.1 ΁ 24 months. Insulin growth factor 1 levels were significantly lower than normal. Fifty percent of the patients had levels lower than normal, but there was no correlation of IGF-I with NYHA class and EF. Testing of the thyroid hormones revealed that TSH levels were similar between patient and controls though 40% of the patients had elevated TSH levels. Of these patients, 5% (1) had hypothyroid. In addition to this, 10% (2) had isolated low T3, suggestive of the low T3 syndrome. None of the thyroid abnormalities showed a correlation with NYHA class or EF. All other hormone concentrations were comparable in both groups. Conclusion: In this cohort of female patients with DCM, circulating concentrations of IGF-I was significantly lower than in healthy controls, most likely as a result of chronic disease. Some patients had serum evidence of hypothyroidism and some with isolated low T3 levels. Other hormone levels were normal including blood glucose, insulin, and prolactin.